Pre-service teachers' approaches to gender-nonconforming children in preschool and primary school: Clinical and educational implications. Issue 2 (3rd April 2019) - Bochicchio, Vincenzo; Perillo, Pascal; Valenti, Antonella; Chello, Fabrizio; Amodeo, Anna Lisa; Valerio, Paolo; Scandurra, Cristiano
Abstract: Corrective approaches taken by teachers towards gender nonconformity in childhood may increase the gender pressure that children feel, negatively affecting well-being and development. This study was aimed at assessing whether the approaches of 305 pre-service preschool and primary school teachers towards gender nonconformity in childhood are influenced by sexist and homophobic attitudes and feelings. The results indicated that the majority of the sample would adopt a supportive and affirmative approach towards gender nonconformity in childhood. Notwithstanding, the results also showed that sexism influenced the likelihood of adopting corrective approaches only to gender-nonconforming primary school children, whilst homophobia was positively associated with adoption of a corrective approach to gender nonconformity in both preschool and primary school children. Suggestions for educational and clinical practice are discussed.